ADVANCE STAGE OF HODGKIN LYMPHOMA SHOWS HIGH DENSITY OF PLASMA CELLS BUT LOW ANGIOGENESIS - Krisna Murti; Neti Neti; Iche Andriyani Liberty (Fakultas Kedokteran Universitas Sriwijaya, 2023)
BackgroundTumor microenvironmental of classical Hodgkin lymphoma (cHL) containing plasma cells and angiogenesis, however their exact roles remained indeterminate. Plasma cells are important prognostic factors of various malignancies. Angiogenesis can be assessed by evaluating of micro vessel density (MVD). Higher MVD is associated with a poor prognosis in various type of malignancies. The objectives of this study were to investigate the density of plasma cells and MVD in the microenvironment of cHL and to determine the association of both components with the stage of cHL.Materials and methodsThe selected 37 paraffin blocks of cHL cases were sectioned. The clinical staging was performed using modification of Ann Arbor staging system. To assess the density of plasma and endothelial cells, anti-CD138 and anti-CD34 antibodies were employed by immunohistochemistry. The association of plasma cells’densities and MVD with cHL stages was measured by statistical analysis using t-test by STATA version 15 with significant consideration if p <0.05.ResultsIn our cohort cHL was occurred in slightly older patients (?40 years; 53.33%), more in male (60%), and majority with nodal location (86.67%). The subtypes was dominated by lymphocyte rich (43.33%); followed by nodular sclerosing (30%) and mixed cellularity (26.67%), while lymphocyte depleted was not found. Statistical analysis revealed that higher density of plasma cells was significantly correlated to the patient higher stages (p=0.0003). While density of micro vessels is not significant correlation (p=0.5564) to the stages of cHLConclusionHigh densities of plasma cells but not angiogenesis correlate to advance stage of Hodgkin lymphoma.